2011
DOI: 10.1586/erd.10.66
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive robotic mitral valve surgery

Abstract: Over the past two decades, significant advances have been made in mitral valve surgery. Cardiac surgeons have successfully repaired degenerative and ischemic regurgitant mitral valves via a traditional midline sternotomy. In recent years, alternate incisions have yielded minimally invasive approaches to the mitral valve. Technological advances have made robotically assisted minimally invasive mitral valve surgery feasible. Decreased pain, more rapid return to work, diminished blood loss and reduced length of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Less-invasive valve surgery has proved even more promising than less-invasive coronary bypass procedures because simpler anastomoses are required. The feasibility and safety of robotic mitral valve replacement (MVR) has been proven in several studies, [1][2][3] with the main goals of improved cosmesis and less postoperative discomfort while maintaining the same level of safety and efficacy as with conventional surgery. However, robotically assisted MVR demands different surgical skills in the implant of the prosthesis.…”
mentioning
confidence: 99%
“…Less-invasive valve surgery has proved even more promising than less-invasive coronary bypass procedures because simpler anastomoses are required. The feasibility and safety of robotic mitral valve replacement (MVR) has been proven in several studies, [1][2][3] with the main goals of improved cosmesis and less postoperative discomfort while maintaining the same level of safety and efficacy as with conventional surgery. However, robotically assisted MVR demands different surgical skills in the implant of the prosthesis.…”
mentioning
confidence: 99%
“…In the paper by Cerny et al which presents a multicenter analysis of robotically assisted cardiac surgery in Europe, it is shown that the conversion rates are convincingly low and that clinical outcomes are favourable ( 13 ). Better postoperative outcomes have also been demonstrated with robotic mitral valve surgery compared to conventional mitral valve replacement before ( 14 16 ). The combination of robotic surgery with electrically induced ventricular fibrillation was used for both primary and redo mitral valve cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks in part to the acquisition of advanced laparoscopic skills and improved instrumentation, nearly all fields of surgery have seen the open counterpart achieved through minimal access surgery. As a result, reduction of hospital stay, improvement in cosmetic results, and decreased postoperative pain has been demonstrated in nearly all the surgical specialties when compared with conventional open operations [].…”
Section: Introductionmentioning
confidence: 99%